Studies on the suitability of certain culture media for Beauveria bassiana (Bals.) Vuill., and Verticillium lecanii (Zimm.) Viegas - A, Karthikeyan; V, Selvanarayanan (Journal of Research in Biology, 2011)
The entomopathogenic fungi, Beauveria bassiana (Bals.) Vuill. and Verticillium lecanii (Zimm.) Viegas are capable of infecting a wide range of insect pests and show promise in commercialization. This laboratory study was made at the Department of Entomology, Faculty of Agriculture, Annamalai University, Tamilnadu, India during 2008-2009 to evaluate the suitability of certain culture media for these fungi. Three synthetic media viz., Potato Dextrose Agar (PDA), Czapek’s Dox Agar (CDA), Rose Bengal Agar (RBA) and three natural substrates viz., water hyacinth, rice bran and spent mushroom paddy straw were chosen. The suitability of the medium was assessed based on the specific parameters namely colony growth in diameter, spore density and biomass production. The maximum colony growth attained by B. bassiana (42.00 mm) and the highest spore density (4.52 ´ 107 spores/ml) and biomass production (466.33 mg) were obtained in the synthetic medium, PDA. Among natural substrates, rice bran amended medium achieved the highest colony growth (46.33 mm) and yielded more spore density of 4.86 ´ 107 spores/ml and the biomass of 485.00 mg. The yielded spores were bioassayed against Spodoptera litura Fab. which exerted 73.33 per cent mortality. V. lecanii achieved the maximum colony growth (47.67 mm) and spore density of 4.73 ´ 107 spores/ml and biomass of 484.67 mg on RBA and on rice bran, it is recorded as 48.67 mm, 5.06 ´ 107 spores/ml and 492.52 mg, respectively. The mortality of Aphis gossypii was 93.33 and 100.00 per cent when treated with V. lecanii grown on RBA and rice bran respectively.